Hubungan antara Menonton Iklan Layanan Masyarakat Vaksin Covid-19 dengan Minat Viewer dalam Melakukan Vaksin - Diaz Septino Rahmat; Zulfebriges (Bandung Conference Series: Communication Management, 2023)
Abstract. The background of this research is based on the issuance of Presidential Decree No. 99 of 2020 which contains Vaccine Procurement and Vaccination Implementation in the Context of Overcoming the Global Covid-19 Pandemic. The YouTube channel of the Directorate of Health Promotion and Community Empowerment of the Ministry of Health of the Republic of Indonesia is a forum for the promotion of covid-19 vaccination. The purpose of this study was to find out whether there was a relationship between the frequency of watching public service advertisements for the covid-19 vaccine with viewer interest in doing vaccines, to find out whether there was a relationship between the duration of watching public service advertisements for the covid-19 vaccine with viewer interest in doing, to find out whether there was a relationship between the intensity of watching public service advertisements for the covid-19 vaccine with viewer interest in doing. The results of the study show that there is a relationship between the frequency of watching public service advertisements for the covid-19 vaccine and the viewer’s interest in administering the vaccine with a correlation value of 0.606. There is a relationship between duration of watching public service advertisements for the covid-19 vaccine and the viewer’s interest in administering the vaccine with a correlation value of 0.545. There is a relationship between intensity of watching public service advertisements for the covid-19 vaccine and the viewer’s interest in administering the vaccine with a correlation value of 0.684.Abstrak. Latar belakang penelitian ini di dasari pada diterbitkannya Perpres No.99 Tahun 2020 yang didalamnya memuat tentang Pengadaan Vaksin dan Pelaksanaan Vaksinasi Dalam Rangka untuk Penanggulangan Pandemi Global Covid-19. Channel YouTube Direktorat Promosi Kesehatan dan Pemberdayaan Masyarakat Kementerian Kesehatan Republik Indonesia merupakan wadah untuk sarana promosi vaksinasi covid-19. Tujuan penelitian ini diantaranya untuk mengetahui apakah terdapat hubungan antara frekuensi menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam melakukan vaksin, untuk mengetahui apakah terdapat hubungan antara durasi menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam melakukan vaksin, untuk mengetahui apakah terdapat hubungan antara intensitas menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam melakukan vaksin. Hasil penelitian menunjukkan bahwa terdapat hubungan antara frekuensi menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam menggunakan vaksin dengan nilai korelasi sebesar 0,606. Terdapat hubungan antara durasi menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam menggunakan vaksin dengan nilai korelasi sebesar sebesar 0,545. Terdapat hubungan antara intensitas menonton Iklan Layanan Masyarakat vaksin covid-19 dengan minat viewer dalam menggunakan vaksin dengan nilai korelasi sebesar 0,684.